Feasibility Study, Design, and Installation of Solar PV Tree to Cover the Electricity Demand at Mangrove Park - Karnoto Karnoto; Denny Nugroho Sugianto; Ariana Aisa; Pangestuningtyas Diah Larasati (Universitas Diponegoro, 2026)
To mitigate climate change, transitioning from fossil fuels to renewable energy sources and expanding carbon sinks such as forests and mangroves are essential strategies. This study explores the integration of solar photovoltaic (PV) tree technology to achieve a net-zero emission concept within the mangrove conservation area at Science Techno Park (STP), Teluk Awur, Jepara, Indonesia. Mangroves play a critical role in carbon sequestration, yet limited land availability for conventional solar panels in such ecosystems necessitates innovative solutions. Solar PV trees, designed with a capacity of 50 Wp per unit and 10 Wp panels per leaf, are deployed to supply electricity for LED lighting (6 W) and mobile charging stations. A total of 70 units, yielding 3500 Wp, are planned for the mangrove boardwalk. Several factors influencing system performance, including non-optimal solar incidence angles, ambient temperature, and dust accumulation, are analyzed due to their potential to reduce efficiency and induce hotspot formation. The installation of a prototype banana-style solar PV tree results in a Net Present Cost (NPC) of USD 828 and a Levelized Cost of Energy (LCOE) of USD 1.080/kWh. The findings demonstrate that solar PV trees offer a feasible and sustainable solution to meet local energy needs while enhancing renewable energy implementation in ecologically sensitive areas.